2016
DOI: 10.1371/journal.pntd.0005026
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected Dengue as a Cause of Acute Febrile Illness in Children and Adults in Western Nicaragua

Abstract: BackgroundDengue is an emerging infectious disease of global significance. Suspected dengue, especially in children in Nicaragua’s heavily-urbanized capital of Managua, has been well documented, but unsuspected dengue among children and adults with undifferentitated fever has not.Methodology/Principal FindingsTo prospectively study dengue in semi-urban and rural western Nicaragua, we obtained epidemiologic and clinical data as well as acute and convalescent sera (2 to 4 weeks after onset of illness) from a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…From Table 1, dengue fever and scrub typhus were the major causes of patient hospitalized FUO. The results were similar to other studies that found dengue was responsible for febrile illnesses in sub-Saharan Africa and other countries [8][9][10]. A study in Rajasthan, India [11] presented 49.1% of patients with FUO that were confirmed by scrub typhus immunoglobulin M antibodies by ELISA and had a similar result to another prospective study among patients with FUO in Chennai City, South India [12], presenting 23% of patients positive for immunoglobulin M antibodies against Orientia tsutsugamushi.…”
Section: Discussionsupporting
confidence: 88%
“…From Table 1, dengue fever and scrub typhus were the major causes of patient hospitalized FUO. The results were similar to other studies that found dengue was responsible for febrile illnesses in sub-Saharan Africa and other countries [8][9][10]. A study in Rajasthan, India [11] presented 49.1% of patients with FUO that were confirmed by scrub typhus immunoglobulin M antibodies by ELISA and had a similar result to another prospective study among patients with FUO in Chennai City, South India [12], presenting 23% of patients positive for immunoglobulin M antibodies against Orientia tsutsugamushi.…”
Section: Discussionsupporting
confidence: 88%
“…aegypti was found in rural regions [ 65 ] south of Bogotá. In Nicaragua, a study showed the unsuspected presence of dengue cases in those areas as well [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of 187 women, 176 (94%) were ZIKV IgG ELISA positive (Table 2), consistent with high DENV prevalence and poor specificity of ELISA. [26] Using a combination of ELISA and neutralization testing ("Integrated Result"), the overall ZIKV seroprevalence at the time of delivery in this population was estimated to be 59% (Table 2). To validate our method for determining ZIKV seroprevalence, 85 delivery specimens were blindly tested at an independent laboratory using ZIKV NS1 BOB.…”
Section: Seroprevalence Of Zikv Infectionmentioning
confidence: 99%